Plant Sciences Reviews 2010 - Hemming, David; Ebooks Corporation (Wallingford : CABI, 2011)
"Plant Sciences Reviews 2010" provides scientists and students in the field with timely analysis on key topics in current research. Originally published online in "CAB Reviews," this volume makes available in printed form the reviews in plant sciences published during 2010.
Contenido: 10. A review of research on forest-related environmental markets (including certification schemes, bioenergy, carbon markets and other ecosystem services)11. Bt plants and effects on soil micro-organisms; 12. Assessing biosafety of GM plants containing lectins; 13. Rice hoja blanca: a complex plant{80}{93}virus{80}{93}vector pathosystem; 14. Plants as reservoirs for human enteric pathogens; 15. Predic
Libro electronico adquirido a perpetuidad con la editorial CABI
Keywords: BIOTECNOLOGIA AGRICOLA; BIOTECNOLOGIA VEGETAL; BOTANICA; INGENIERIA GENETICA VEGETAL